The good, the bad, and the (sometimes) ugly truths: American penal goals and perspectives - Tewksbury, Richard (American journal of criminal justice, 2003)
Identifying correctional objectives and evaluative criteria is essential to facilitating smooth operational functioning of the correctional system. Complicating this necessity is the tremendous growth and responsibilities of the correctional system as budgets continue to suffer reductions or stagnations. Traditional evaluative studies producing valuable insights, have yet to, for the most part, move beyond recidivism and incarceration rates as performance indicators. This is due mostly to the fact that criminal justicians — scholars and practitioners — and the general public lack consensus regarding correctional goals. Instead, what we are experiencing is an ambivalence placing an unfair burden upon the correctional system to create and maintain effective rehabilitative programs, devise punitive strategies, and fulfill these countervailing missions with decreased financial resources than in the past (relative to case load). To be sure, wardens and correctional administrators are called upon today to do more with drastically fewer dollars. The correctional system, we argue, given its unique task of incapacitating people, demands that scholars, practitioners, and policymakers combine efforts to develop correctional goals. These goals once defined, however, are not to become fixed static categories. Instead, they must remain flexible and imitate or adapt to social and cultural conditions, which is not to say merely reflect public opinion. Rather, correctional goals must consider legal, normative, and other structural changes affecting the correctional system — as many scholars recognize these variables having greater impact on incarceration (see Christie, 2000; Dilulio, 1993; Garland, 2001). This joint effort should take advantage of research-based knowledge and examples of best practices to identify the good aspects, weed out the bad, and eliminate the ugly in the U.S. penal system.